Andrological problems in patients with spinal cord injuries. - Ronzoni, G.; De Giovanni, L.; Spagnolo, A. G. (Medicina e Morale, 1995)
Starting from a case report, the article presents the andrological problems of paraplegic men, from a clinical and ethical point of view. The most often reported andrological disorders are those regarding erection and fertility. This produces a "handicap within the handicap", with all the understandable discomforts relative to the management of sexuality in a marriage. The authors therefore consider necessary both to give the patient a serious and motivated medicai answer and the physician should seriously consider not only patient's clinical aspects but also his ethical dirnension, given the absoluteness of the unitary vision of the human person. Therefore, the diagnosis and therapy are to be placed in a context of sexual health, excluding a priori any simply hedonistic intervention. Several values are involved in the andrological dysfunction of paraplegic men: a. the protection of the dignity of the human person above ali in relation to privacy and informed consent; b. the opportunity to encourage the couple to approach the problem together as much as possible; c. the therapeutic principle; d. the obligation to provide suitable therapeutic standards. The article continues by illustrating the pharmacological and surgical therapies of the erection dysfuction with a detailed analysis of the ethical values involved. The fact that the ethical acceptability of these interventions should be considered in relation to the therapeutic principle is also mentioned. Moreover, the aspect regarding the implications for married life in these particular situations is also dealt with. In conclusion the Urosurgery for Paraplegics Section, which was set up in 1992 at the Department of Urology at the Catholic University in Rome, is presented as a response to medicine's duty to also take care of these particular problems of paraplegic men.